2015
DOI: 10.1108/ccij-09-2013-0056
|View full text |Cite
|
Sign up to set email alerts
|

Company slogans, morphological issues, and corporate communications

Abstract: Purpose -The purpose of this paper is to investigate and analyze company slogans which play an important role in corporate identity and corporate communications. Design/methodology/approach -By discussing relevant literature, morphological issues (word formation in sentences), and content analysis, the study investigates 329 companies and their slogans that operate in global and domestic markets. Findings -The study finds that within the areas of corporate identity and corporate communications, company slogans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
8
0
4
Order By: Relevance
“…Así, en el sector de la alimentación se demuestra que las imagines (percepciones) generadas por el consumidor influyen en su elección de comida más o menos saludable (Coary y Poor, 2016), en las marcas relacionadas con la moda se definen dimensiones de la imagen concretas desde el aspecto cognitivo, emocional, sensorial y de autoexpresión (Cho y Fiore, 2015) y encontrar relaciones entre los eslóganes con la imagen corporativa y el valor de marca producto (Anwar, 2015).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Así, en el sector de la alimentación se demuestra que las imagines (percepciones) generadas por el consumidor influyen en su elección de comida más o menos saludable (Coary y Poor, 2016), en las marcas relacionadas con la moda se definen dimensiones de la imagen concretas desde el aspecto cognitivo, emocional, sensorial y de autoexpresión (Cho y Fiore, 2015) y encontrar relaciones entre los eslóganes con la imagen corporativa y el valor de marca producto (Anwar, 2015).…”
Section: Resultsunclassified
“…Se han considerado las fuentes que se centran en el concepto de marca desde distintas perspectivas. Estos elementos apuntan a la Identidad (Aaker, 2002(Aaker, , 2005aBalmer 2012;Keller, 2006;Melewar y Karaosmanoglu, 2006;Cho y Fiore, 2015;Coary y Poor, 2016;Bernabel, 2016), Posicionamiento (Balmer, 2012; Álvarez del Blanco, 2012; Kachersky y Carnevale, 2015) e Identidad formal (Costa, 2006;Anwar, 2015;Hakala et al, 2015;Machado et al, 2015).…”
Section: Introductionunclassified
“…While slogans are known to enhance brand equity, its use in practice appears to vary. From an overall industry perspective, only 28% of companies found on Business Week’s list of largest market capitalization firms and 21% of companies found on the Fortune 500 list used slogans (Anwar, 2015; Miller and Toman, 2015). Results are strikingly different within the tourism industry where more than 92% of US states (Lee et al , 2006; Richardson and Cohen, 1993) and 76% of Caribbean countries were found to use slogans (Miller and Henthorne, 2006).…”
Section: Studymentioning
confidence: 99%
“…Brand name gives to the product its core identity and logos serve as visual cues for processing brand recognition. In addition, slogans might also be important in branding Toman, 2014 and2015) with a supplemental role to brand names and logos, since they might contribute to the brand equity, improving its awareness, image and positive associations (Dahlén & Rosengren, 2005). So, it is possible to conclude that a slogan might contribute to build or reinforce the image, identity or position for a brand by trying to increase its memorability (O'guinn et al, 2011).…”
Section: Slogan Concept and Slogan Roles Within Brand Managementmentioning
confidence: 99%
“…On corporate identity and corporate communications. brand name, logos and slogans might act as one (Anwar, 2015). Brand name gives to the product its core identity and logos serve as visual cues for processing brand recognition.…”
Section: Slogan Concept and Slogan Roles Within Brand Managementmentioning
confidence: 99%